Using visual representations to realise the concept of "heat". (2nd January 2020) - Yeo, Jennifer; Wong, Wai Lit; Tan, Daniel K. C.; Ong, Yann Shiou; Delserieys Pedregosa, Alice
ABSTRACT: Science teachers often use visual images to help students visualise the abstract concepts of science. Yet, they may not support students in making sense of these visual representations, wrongly assuming that the students can intuitively do it on their own. Pre- and in-service teacher professional development programmes also seldom explicitly teach how visual representations can be purposefully selected and utilised to help students comprehend abstract concepts of science. Thus, the aim of this study is to examine how an elementary science teacher made use of visual representations to realise the meaning of the concept of "heat", and to identify design considerations when using visual representations for concept teaching. Using multimodal analysis, the findings showed how the teacher orchestrated a sequence of ensembles of visual representations which bore conceptual, pedagogical, and epistemological roles in unpacking the concept of "heat" to facilitate his students' understanding. The findings indicate the importance of teachers developing representation-content-pedagogical competences in order to select representations apt for the targeted content knowledge, the students' profile, the learning environment, and the nature of the science.